2013
DOI: 10.1097/mlr.0b013e31829a4f92
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health Assessed by Web Versus Mail Modes in a Mixed Mode Survey

Abstract: The alignment between survey mode selection, Internet access, and health disparities, as well as genuine survey mode characteristics, leads to web-mail differences in SRH. Unless the digital divide and its influences on survey mode selection are resolved and differential genuine mode effects are fully comprehended, we recommend that both modes be simultaneously used on a complementary basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…We confirmed the so-called “digital divide” [ 47 - 50 ]—male adolescents and younger fathers preferred the online mode, a well-known systematic difference [ 5 ] between these modes[ 10 , 49 , 51 - 54 ]. Additionally, SAQ-Web respondents had higher household incomes [ 15 , 49 , 55 ] and higher household education levels [ 10 , 49 , 54 - 57 ]. Despite these differences, and differences in online response rates between the mixed-mode survey designs, there were no statistically significant differences in sample composition between the paper-and-pencil single-mode control group and the 3 mixed-mode groups.…”
Section: Discussionsupporting
confidence: 71%
“…We confirmed the so-called “digital divide” [ 47 - 50 ]—male adolescents and younger fathers preferred the online mode, a well-known systematic difference [ 5 ] between these modes[ 10 , 49 , 51 - 54 ]. Additionally, SAQ-Web respondents had higher household incomes [ 15 , 49 , 55 ] and higher household education levels [ 10 , 49 , 54 - 57 ]. Despite these differences, and differences in online response rates between the mixed-mode survey designs, there were no statistically significant differences in sample composition between the paper-and-pencil single-mode control group and the 3 mixed-mode groups.…”
Section: Discussionsupporting
confidence: 71%
“…These findings support previous research suggesting that self-reports on global health do not vary between the different kinds of self-administered modes [ 16 ]. However, Shim et al [ 46 ] found that web respondents report better self-rated health than SAQ-Paper respondents. Because of this inconsistency, further research on differences in reports on global health between paper-based and web-based questionnaires is required.…”
Section: Resultsmentioning
confidence: 99%
“…One notable exception is a recent experiment using the Pew Research Center's American Trends Panel, showing that respondents interviewed over the phone were more likely to report "excellent" (and less likely to report "very good" or "good") health compared to web respondents (Pew Research Center 2015). In addition, in the Gallup Panel 2008 Health Survey, web respondents had better SRH than mail respondents (after controlling for relevant covariates associated with Internet access) (Shim, Shin, and Johnson 2013). Further research is needed that compares the distribution of SRH and its association with covariates across other modes and across survey measurement features within a mode (e.g., horizontal or vertical presentation of response options in a self-administered mode [Garbarski, Schaeffer, and Dykema 2015b]), and that also incorporates respondents' characteristics such as cognitive ability and socioeconomic status.…”
Section: Features Of Survey Measurement Of Srhmentioning
confidence: 99%
“…For example, the General Social Survey uses a version with "excellent, good, fair, or poor," and the Gallup Panel qualifies "fair" with "only" (Shim, Shin, and Johnson 2013); many other surveys also include "very good" between "good" and "excellent." Including more response options may make sense in order to capture finer gradations in health, particularly positive options such as "very good" to obtain more discrimination in populations that are healthier or that view health optimistically, but this claim warrants empirical investigation (Smith 2005).…”
Section: Features Of Survey Measurement Of Srhmentioning
confidence: 99%